2013
DOI: 10.1093/ageing/aft008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of telecare on use of health and social care services: findings from the Whole Systems Demonstrator cluster randomised trial

Abstract: Objective: to assess the impact of telecare on the use of social and health care. Part of the evaluation of the Whole Systems Demonstrator trial.Participants and setting: a total of 2,600 people with social care needs were recruited from 217 general practices in three areas in England.Design: a cluster randomised trial comparing telecare with usual care, general practice being the unit of randomisation. Participants were followed up for 12 months and analyses were conducted as intention-to-treat.Data sources: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 12 publications
3
79
1
Order By: Relevance
“…The results from telecare studies differ substantially as some reports that telecare appears to support older people to remain at home 2,3 , while others show opposite results 4 . Previous research raises several questions about the slow uptake and identifies users' acceptance of telecare to be a key issue [5][6][7][8] .…”
Section: Introductioncontrasting
confidence: 67%
“…The results from telecare studies differ substantially as some reports that telecare appears to support older people to remain at home 2,3 , while others show opposite results 4 . Previous research raises several questions about the slow uptake and identifies users' acceptance of telecare to be a key issue [5][6][7][8] .…”
Section: Introductioncontrasting
confidence: 67%
“…This article adds to the growing set of publications 12,[20][21][22][23][24] by the Whole System Demonstrator evaluation team and provides a unique insight into some of the challenges facing front-line professionals within the larger study. While the study was completed some time ago, it is unlikely that views will have fundamentally altered as little progress (in terms of large scale implementation) has been made and most healthcare staff will not have come across this technology.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…While some research has illustrated how telecare can allow people to stay in their own homes for longer and forgo the immediacy of institutional care (Gordon, 1993;Mynatt et al, 2001) promote independence (Price, 2007) and reduce financial costs (Blythe et al, 2005;Meng & Lee, 2006), the empirical evidence is weak. Recent findings from the largest randomized control trial of telecare in the world, involving 2600 participants in 3 areas of England over a 12-month period found that it did not significantly alter rates of health and social care use or mortality (Stevenson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%